Investigação das propriedades do bulk e da superfície do ZnS e CdS: uma abordagem computacional - Favaretto, Luana Ranubia da Silva (2018)
The computational design of new nanoscale functional materials offers an understanding, fundamental from a modern structural perspective that in turn makes possible to improve its properties and applications. In this sense, the study of the structural and electronic order-disorder effects in semiconductor materials, particularly suggests an "intuitive" way to understand the chemical behavior of these important materials, being, therefore, an attractive area of research in materials science and engineering, since these a priori strongly govern their physical and chemical properties of great interest in various technology applications. In this context metallic sulfides such as zinc sulfide (ZnS) and cadmium (CdS) are considered to be promising semiconductor materials because they have relevant physical and chemical properties that make them attractive for the development of many technological applications, such as electronics, optoelectronics, photocatalytics and others. Thus, this work will focus on the theoretical and computational study, based on the formalism of the theory of density functional (DFT), on the structural, electronic and vibrational properties of ZnS and CdS bulk. Particularly, the structure studied was cubic, known as zinc blende, as well as the surfaces were in the directions (100), (110) and (111), respectively for both systems. The properties of both the bulk and the abovementioned surfaces for ZnS and CdS were analyzed as a function of state density (DOS), band structure, vibrational modes, surface energy, as well as order effects - structural and electronic disruption of these materials in their bulk form, in order to try to elucidate the origins of their exotic properties at nanometer scale. All calculations of this project were performed under periodic conditions using the CRYSTAL program 17. The results were compared directly with experimental data available for both systems. The band gap value obtained for the ZnS was 3,58 eV, of the CdS was, of 3,12 eV, both with a direct gap.